Effectivity of the SPEOS Method and the Marmet Technique Combination on the Milk Ejection of Postpartum Women - Nuryani Nuryani; Ayesha Hendriana Ngestiningrum; Nurwening Tyas Wisnu (Humanistic Network for Science and Technology (HNST), 2021)
Breastmilk is the most important food for babies, especially in the first months of their lives. There is usually the problem of milk ejection on the first day after giving birth. The development of the SPEOS Method and the Marmet Technique may be used to aid postpartum women on the breastmilk ejection, considering that the provision of exclusive breastmilk is highly dependent on the first days after birth. This study used the quasi-experiment design with the posttest only design with a control group. The population was postpartum women in the area of Lembeyan Community Health Center with the Consecutive sampling technique. The sample 40 mother (10 mother in in SPEOS group, 10 mothers in Marmet group, 10 mothers in Combination SPEOS and Marmet group, and 10 mother in control group). The independent variable was the combination of the SPEOS Method and the Marmet Technique. The dependent variable was the breastmilk ejection on postpartum women and the increase of the babies’ weight. Breat milk data were collected by questionare and the babies’s weight collected in 7th day. The results of the research showed that the combination of the SPEOS Method and the Marmet Technique is effective in increasing the breastmilk ejection and in increasing the babies' weight, with the significant value of the Manova test (p-value = 0.000). The combination of the SPEOS Method and the Marmet Technique is highly effective in increasing milk production and baby weight. Keywords: SPEOS method; marmet technique; breastmilk expresion; baby weight